Efficient public key encryption with equality test in the standard model - Zhang, Kai (2020)
Public key encryption with equality test (PKEET) is a special kind of public encryption scheme (PKE) that allows a tester to perform equality tests on ciphertexts generated by different public keys as well as the same public key. This feature enables us to apply PKEET to various scenarios in practice, such as efficient data management on encrypted databases and spam filtering in encrypted email systems. From these reasons, since Yang et al. [1] first proposed the concept of PKEET, there have been proposed many PKEET schemes to improve efficiency or to enhance functionalities. However, to the best of our knowledge, almost all existing schemes were presented under assuming the existence of random oracles, except for generic construction proposed by Lee et al. On the other hand, their generic approach for PKEET employs a 2-level hierarchical identity-based encryption and a strongly unforgeable one-time signature, which suffers from low efficiency. In this paper, we propose an efficient PKEET scheme under a specific cryptographic assumption in the standard model. To this end, we first encrypt a message and its hash value in a parallel way by following the recently proposed strategy. Then, to prevent adaptive chosen ciphertext attacks (CCA2), we give a link between them by adapting the technique which was originally proposed for identity-based encryption and previously exploited to design efficient CCA2-secure PKE schemes. We show that our proposed construction satisfies formal security requirements for PKEET under the decisional bilinear Diffie–Hellman (DBDH) assumption in the standard model. As a result, we obtain a new PKEET scheme which has shorter ciphertext and trapdoor sizes, and improves computational costs for encryption, decryption, and test algorithms, by about 60%, 77%, and 66%, respectively, compared to a PKEET instantiation obtained by the prior generic framework.